Reclaimed Water for Homeowner Irrigation - Lawrence R. Parsons (EDIS, 2009)
HS1157, a 5-page illustrated fact sheet by Lawrence R. Parsons, describes what reclaimed water is, what it can be used for, advantages, safety, use in edible crops, salinity, and plant nutrients. Published by the UF Department of Horticultural Sciences, July 2009.